Multiplexed CRISPR/Cas9-mediated knockout of 19 Fanconi anemia pathway genes in zebrafish revealed their roles in growth, sexual development and fertility - Ramanagoudr-Bhojappa, Ramanagouda (PLoS Genet, 2018)
Fanconi Anemia (FA) is a genomic instability syndrome resulting in aplastic anemia, developmental abnormalities, and predisposition to hematological and other solid organ malignancies. Mutations in genes that encode proteins of the FA pathway fail to orchestrate the repair of DNA damage caused by DNA interstrand crosslinks. Zebrafish harbor homologs for nearly all known FA genes. We used multiplexed CRISPR/Cas9-mediated mutagenesis to generate loss-of-function mutants for 17 FA genes: fanca, fancb, fancc, fancd1/brca2, fancd2, fance, fancf, fancg, fanci, fancj/brip1, fancl, fancm, fancn/palb2, fanco/rad51c, fancp/slx4, fancq/ercc4, fanct/ube2t, and two genes encoding FA-associated proteins: faap100 and faap24. We selected two indel mutations predicted to cause premature truncations for all but two of the genes, and a total of 36 mutant lines were generated for 19 genes. Generating two independent mutant lines for each gene was important to validate their phenotypic consequences. RT-PCR from homozygous mutant fish confirmed the presence of transcripts with indels in all genes. Interestingly, 4 of the indel mutations led to aberrant splicing, which may produce a different protein than predicted from the genomic sequence. Analysis of RNA is thus critical in proper evaluation of the consequences of the mutations introduced in zebrafish genome. We used fluorescent reporter assay, and western blots to confirm loss-of-function for several mutants. Additionally, we developed a DEB treatment assay by evaluating morphological changes in embryos and confirmed that homozygous mutants from all the FA genes that could be tested (11/17), displayed hypersensitivity and thus were indeed null alleles. Our multiplexing strategy helped us to evaluate 11 multiple gene knockout combinations without additional breeding. Homozygous zebrafish for all 19 single and 11 multi-gene knockouts were adult viable, indicating FA genes in zebrafish are generally not essential for early development. None of the mutant fish displayed gross developmental abnormalities except for fancp(-/-) fish, which were significantly smaller in length than their wildtype clutch mates. Complete female-to-male sex reversal was observed in knockouts for 12/17 FA genes, while partial sex reversal was seen for the other five gene knockouts. All adult females were fertile, and among the adult males, all were fertile except for the fancd1 mutants and one of the fancj mutants. We report here generation and characterization of zebrafish knockout mutants for 17 FA disease-causing genes, providing an integral resource for understanding the pathophysiology associated with the disrupted FA pathway.